The Application of Ultrasonography in the Detection of Airway Obstruction: A Promising Area of Research or Unnecessary Gadgetry? - Sabina Kostorz-Nosal; Mariusz Kowaliński; Aleksandra Spyra; Bartłomiej Gałuszka; Szymon Skoczyński (Life)
Since the COVID-19 pandemic, the utilization of transthoracic ultrasonography (TTU) in the evaluation of pulmonary field artefacts has become standard practice among clinicians. However, there is a considerable lack of knowledge regarding the assessment of diaphragm mobility in the context of various lung diseases. Although numerous conditions are known to affect diaphragm mobility, including neurological, cardiovascular, and infectious diseases, it appears that pulmonary diseases may also limit the mobility of this major respiratory muscle. Despite the evidence of diaphragm mobility disorders in patients diagnosed with lung cancer, there is a discrepancy in the literature regarding the function of the diaphragm in individuals with chronic obstructive pulmonary disease (COPD). A shared aetiological factor frequently results in the co-occurrence of the aforementioned diseases. It is, however, possible to detect patients whose obstructive airway disease is caused only by the compression of infiltrative and nodal lesions rather than COPD. Bilateral TTU of diaphragmatic mobility in correlation with other available pulmonary function tests and radiological imaging may prove to be a valuable approach to isolating lung cancer patients with COPD overdiagnosis. Conversely, the overdiagnosis of COPD has been implicated in the potentially unnecessary and harmful use of inhaled medications with their adverse effects (e.g., cardiac arrhythmias, limb tremor, cough, and pneumonia), the failure to decrease obstruction in cases of other lung disorders, and the potential to contribute to the delayed diagnosis of the underlying condition responsible for the respiratory symptoms. This paper aims to provide a comprehensive overview of the utilization of ultrasound in the evaluation of diaphragm movement impairments for the detection of obstructions while also delineating the underlying limitations of this technique. Moreover, we propose a diagnostic algorithm for the purpose of excluding unilateral obstruction resulting from infiltrative neoplastic masses based on the ultrasound assessment of diaphragmatic mobility.